Caracterização de perfis de intemperismo entre as superfícies geomórficas V e II Planalto das Araucárias - Dal-berti, Wanessa Suelen Peloso (2015)
The research presents the characterization of surface formations in the sector covering the geomorphic surfaces IV and III in the Araucária Plateau, including transitions to surfaces II and V, in order identify the stage of materials evolution in representative profiles of each geomorphic surface. For this we used the lifting of macro morphology characteristics of surface, and laboratory analyzes of particle size, macronutrients, sulfuric attack and clays diffractogram of X-rays. The representative profile of the surface IV, developed on basaltic substrate, in surface with elevation between 1000 and 1100m, has over 4 meters thichness and solum more than 230cm, corresponding to Nitossolo Bruno Distroférrico Aluminico. It s mineral matter consists of quartz, anatase, ilmenite, hematite, goethite, gibbsite, kaolinite and possible presence of vermiculite. Between the geomorphic surfaces IV and III, the change of profile is developed on rhyolite, with soil 220cm thick whose morphological characteristics individualize Oxisol Distrofic, aluminum character. The Horizon B mineral matter consists of quartz, anatase, gibbsite, kaolinite and possible presence of VHE (vermiculite hydroxy between layers). The morphological characteristics of this profile indicate evolved weathering stage, although the horizon B has only 55cm. On the surface III, the profile described amendment corresponds to Oxisol Distroferric aluminum, whose mineralogy in the sand and silt fractions are made up of quartz, tridymite, cristobalite, spinel, magnetite, ilmenite, hematite, goethite and it s polimorfo, the lepidocrocite. In the clay fraction occur goethite, hematite, brookita, diaspore, boehmite, kaolinite and diquita, although vermiculite Al-OH between layers (VHE), besides the boehmita and mineral zeolites group. In the transition area between the geomorpfic surfaces V and IV, the changing profile showed 550cm thick, of which 370cm correspond to soil. Presents very weathered material, the type Oxisol Distroferric aluminium, the characteristics of sulfuric attack indicate that volumes appear to have no evolutionary relation with each other, indicating that is not changing material developed in situ. The minerals in the sand and silt fraction are cristobalite, tridymite, magnetite, ilmenite, hematite, goethite and apinel. In the clay fraction occurring minerals similar to those recorded in the B horizon of the representative profile of the surface III. In short, the weathering profile identified in geomorphic surfaces studies (IV, III and transitions) have very similar morphological characteristics indicating overall, high change stage. The four representative profiles analyzed there fall into the class of Oxisol, varying only distrophic,for distroferric, and is presented in Nitossolo Bruno Distroferric aluminium class. Of these profiles, three have development features from indigenous parent material (P1, P4 and P11), while the P13 profile shows parental relation with allochthonous material.